Pemahaman Siswa Terhadap Pembelajaran Daring: Sebuah Studi Kualitatif - Fauzan Sholeh, Rifqi (CV RIFAINSTITUT, 2024)
This qualitative phenomenological study explores students' understanding of online learning in Indonesian secondary education during COVID-19. Using purposive sampling, 18 grade 11 students from three high schools in West Java participated through 60-90 minute semi-structured interviews. Thematic analysis revealed five major themes: (1) sudden transition as pedagogical disruption; (2) redefinition of presence in digital spaces; (3) learner autonomy as new demand; (4) access inequality as determinant; and (5) meaning construction through contextual negotiation. Findings indicate students actively construct understanding through complex negotiations between expectations, material realities, and social interactions. The study identified significant paradoxes including presence paradox and autonomy paradox. Trustworthiness was ensured through triangulation, member checking, and reflexive journaling.